1984
DOI: 10.1159/000233541
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Thymocytes from G1 into S Phase by a Thymic Factor

Abstract: A thymic factor previously shown to stimulate the DNA synthesis of immature thymocytes was found to recruit G1 cells synchronously into S phase within 1.5–2 h. The S + G2 + M duration of the cultured thymocytes was not affected. In the absence of the thymic factor, the responding thymocytes seemed to be blocked in G1 at a putative restriction point 1.5 h prior to S phase. When the addition of the thymic factor to cultured cells was delayed, the responsiveness rapidly declined, indicating that target cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A dose-dependent TGP activity was de tected in an aqueous extract of intact human thymus. Higher activity was recovered from extracts of sus pended thymocytes than from intact thymus, and weaker activity from thymic stroma depleted of thy mocytes, supporting previous results with murine TGP which suggested an autocrine or paracrine growth stimulation of the thymocytes [7], Although hampered by lack of human material, our functional studies aimed to delineate the target cell of human TGP have shown results consistent with those ob tained with bovine TGP [5,15].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A dose-dependent TGP activity was de tected in an aqueous extract of intact human thymus. Higher activity was recovered from extracts of sus pended thymocytes than from intact thymus, and weaker activity from thymic stroma depleted of thy mocytes, supporting previous results with murine TGP which suggested an autocrine or paracrine growth stimulation of the thymocytes [7], Although hampered by lack of human material, our functional studies aimed to delineate the target cell of human TGP have shown results consistent with those ob tained with bovine TGP [5,15].…”
Section: Discussionsupporting
confidence: 87%
“…Previously, a similar activity has been puri fied from bovine thymus and shown to reside in a low-Mr peptide [6]. This bovine TGP acts as a progres sion factor for the main proliferating population in the thymic cortex consisting of immature thymocytes [17,18], regulating their entry from the Gi into the S phase [5], Bovine TGP is a 1.6-kD N-terminal blocked hydrophilic peptide with an isoelectric point of 5.7 [4,6]. The amino acid composition has shown a high content of Glx and Asx residues, but their degree of amidation remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1] and on the basis of studies of DNA synthesis, mitogen stimulation, rosetting, PNA binding, cell volume and buoyant density, the target cell for this factor was shown to be an immunologically immature cell [2,3]. In vitro, TGP allowed the responsive cells to pass a restriction point in G] and to enter S phase and mitosis [4], In vivo, these cells constitute a major fraction of cycling thymo cytes. Another large population of proliferating cells (in guinea pigs distinct from TGP-responsive cells mainly by their inability to form E rosettes) does not respond to TGP, and no growth factor for these cells is known [5,6].…”
Section: Introductionmentioning
confidence: 99%